2006
DOI: 10.1080/01443610600613573
|View full text |Cite
|
Sign up to set email alerts
|

Management of uterine fibroids in Enugu, Nigeria

Abstract: A 5-year review of management of uterine fibroids at the university of Nigeria Teaching Hospital Enugu revealed that symptomatic uterine fibroids constituted 9.8% of all gynaecological admissions. The peak incidence n = 51 (26.8%) was in the age range of 31 - 35 years and the majority of the women n = 77 (40.5%) were nulliparous. The main clinical features were lower abdominal discomfort, menorrhagia and associated infertility. There was no medical management. The surgical management consisted of myomectomy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 5 publications
2
24
2
Order By: Relevance
“…In Nigeria, surgery remains the mainstay of treatment. A study in Enugu showed that 60% of patients with symptomatic uterine fibroid had myomectomy while 36.8% had hysterectomy [2]. These values were similar to findings in Zaria which showed that 62.7% of patients with symptomatic uterine fibroid had myomectomy while 37.3% had hysterectomy [3].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In Nigeria, surgery remains the mainstay of treatment. A study in Enugu showed that 60% of patients with symptomatic uterine fibroid had myomectomy while 36.8% had hysterectomy [2]. These values were similar to findings in Zaria which showed that 62.7% of patients with symptomatic uterine fibroid had myomectomy while 37.3% had hysterectomy [3].…”
Section: Introductionsupporting
confidence: 74%
“…It constitutes 13.4% of all gynaecological admissions in Ilorin [1], while 9.8% of all gynaecological admissions in Enugu are indicated for uterine fibroids [2]. In Enugu, it was found that uterine fibroid was the indication for 26.2% of major gynaecological surgeries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in haemostatic methods and anaesthesia also play an important part in the safety and reduction in mortality and morbidity. Abdominal myomectomies are still predominantly done in the developing world with zero mortalities as was also recorded in this case 19,20,21 . This can also be due to proper case selection without conversion to hysterectomy .…”
Section: Discussionmentioning
confidence: 86%
“…Despite the late presentation, most of these women, when they finally accept surgery and have been able to raise the money for the surgery seek to have abdominal myomectomy despite counseling and despite the risk associated with such a surgery instead of opting for the less risky hysterectomy because of their desire to conserve their reproductive potential [16,17]. Extensive abdominal myomectomy is associated with prolonged anesthesia and surgery times, increased risk of hemorrhage, sepsis, thromboembolism, uterine synechia, intraperitoneal adhesions and intestinal obstruction [3,[18][19][20].…”
Section: Challenges Of Managementmentioning
confidence: 99%